Methods of Increasing Efficiency of Antennas Embedded in Dissipative Media - R. Yu. Borodulin (Известия высших учебных заведений России: Радиоэлектроника, 2017)
The article considers the problem of increasing efficiency for antennas embedded in dissipative media that has limited number of solutions today. The author makes attempts to study the possibility of using plate antennas for different parameters of dissipative media. The research is carried out by means of analytical and computer electromagnetic methods. It makes possible to refine some effects and reveal new patterns. The article provides sound approaches to increase efficiency of antennas embedded in dissipative media. The results are confirmed with numerical calculations. The article presents the methods of increasing efficiency of antennas embedded in soil with different electrical parameters. The results of numerical analysis of antenna length, gain and impedances for embedded antennas of various constructions are given. Comparative analysis of the efficiency of cylindrical and plate antennas is provided. Special considerations of plate antenna construction and their advantages over embedded antennas of different types are revealed.